2017
DOI: 10.1007/s11325-017-1535-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe obstructive sleep apnea treatment with oral appliance: the impact on obstructive, central and mixed events

Abstract: The treatment was effective in reducing obstructive events which were evaluated through the AHI and minimum oxygen saturation. The oral appliances also normalized central and mixed events among patients with severe OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the present study, all patients underwent the baseline and after-treatment polysomnography in the same sleep laboratory in order to standardize the comparison of results. A recent study, published in 2018 17 , also evaluated the efficacy of this appliance, but it focused on evaluating the impacts on central and mixed events. In addition, the polysomnographic exams were not conducted in the same laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, all patients underwent the baseline and after-treatment polysomnography in the same sleep laboratory in order to standardize the comparison of results. A recent study, published in 2018 17 , also evaluated the efficacy of this appliance, but it focused on evaluating the impacts on central and mixed events. In addition, the polysomnographic exams were not conducted in the same laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lingual device also decreased the desaturation events and increased the minimum oxyhemoglobin saturation (SpO 2 ). However, it is important to show the possible side effects of lingual orthosis, such as difficulty swallowing, gagging, vomiting, and injury to the mucosa 17 . To prevent such effects, the lingual device must be carefully titrated, especially when it is necessary to place the spring in a position far below the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive accuracy has shown a broad variability depending on the definitions of success for the treatment 44 . Researchers have found some predictors of success related to treatment with OA such as waist circumference, obesity, overbite, class II division 2 malocclusion 35 . However, in the present study, only baseline AHI proved to be a significant predictor of a complete response rate (AHI <10 / h) during MAD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The objective effective rate was 88.2%, and the effective subjective rate was 93.3% (12). Many clinical studies have confirmed that adjustable dental appliances can change mandibular positioning, effectively increase the airway cross-sectional area, and effectively reduce the respiratory disorder index in OSAS patients (13).…”
mentioning
confidence: 91%